Gambaran Produksi ASI Ibu Post Partum pada Hari 3 Sampai Hari ke 7: Gambaran Produksi ASI Ibu Post Partum pada Hari 3 Sampai Hari ke 7 - Siti Wakhidah (Jurnal Medika Hutama, 2022)
Breast milk is the best food for babies because it contains quality nutrients and becomes the main source of nutrition for babies.This research aims to find out the picture of postpartum maternal breast milk production on the 3rd to the 7th day.The study used a simple descriptive design with a cross sectional approach.The samples used in this study were 100 respondents taken based on inclusion criteria using quota sampling techniques.Use a questionnaire sheet consisting of indicators of breast milk production. The analysis of the data used is univariate to know the frequency distribution.This study describes the age range of the most respondents is 20-35 years (94.0%), the last college education (69.0%), the majority did not work (52.0%), the type of vitamins and lactogog consumed by the mother was vegetables (42.0%), most mothers did not smoke (98.0%), and most of the gestational age (gestur) of the mother was matur (37-42 weeks) by (91.0%).The picture of posrpartum breast milk production on the 3rd to the 7th day is sufficient (55.0%).On the 3rd to 7th day it can be described that postpartum breast milk is sufficient.The results of this study can be used as a reference in health services in providing education or breastfeeding programs to postpartum mothers.Keywords: Adequacy, Postpartum, Breast Milk Production.